Propose Digital Marketing Strategy to Increase Brand Awareness for Fashion Brand Establishment (Case Study in Lune Exterieur) (The Indonesian Journal of Business Administration, 2021)
The creative industry in Indonesia continues to develop over time, especially in the fashion industry, which continues to grow massively. Seeing these developments, the fashion industry and the apparel industry certainly have considerable potential because fashion has become part of the urban lifestyle trend. Many creative industry businessmen nowadays carry out their business activities by utilizing social media and other online platforms to examine the prospect of the target market's behavior that is more dominant by using online consumption activities. Therefore, they must build an excellent strategic process to survive in the competitive fashion market in Indonesia. Lune Exterieur, founded in April 2019, is one of the creative industries in fashion whose business idea is to offer fashion at the best prices in a sustainable manner. In creating a strong brand, Lune Exterieur has to create and build positive activities related to its brand concept to reach the target market created. This study used qualitative research methods by conducting in-depth interviews with customers, business people, and professions related to digital marketing. It then used a SWOT analysis and determined the root causes of the problem by applying cause-diagram-effect (CED) followed by creating strategy development and making strategy implementation plans. The results of this study used content marketing matrix, social media optimization, AIDA models, and tipping points. The overall results were then distributed digitally through all Lune Exterieur social media by using paid advertising services and placing some of the righthuman resources in maximizing the marketing process. The implementation plan contains the time frame for business implementation and provides solutions to digital marketing budgets in the future.Keywords: Digital marketing strategy, content marketing matrix, AIDA model, tipping points.